Preferences Consumers Toward Topo Red Onions (Allium cepa) in North Maluku - Sidayat, Mardiyani; Baguna, Firlawanti; Mahmud, Haris (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
Red onions (Allium cepa) are mostly using in cooking and being one of strategic horticulture commodities in Indonesia. Topo red onions are native plant from Topo-Tidore Island-North Maluku, Indonesia. It has a higher spicy taste compared to other types of red onions and has a fairlystrong essential aroma. This has been cultivated since centuries by the local community in that area. The aim of this study was to identify the preferences consumers toward Topo red onions in North Maluku. The research was conducted in the central market of Tidore, using accidental sampling for 60 respondents who were consumers of Topo red onions. The method used was a survey and interview with likert scale questions. The manalytical method used for this study is descriptive analysis and multiple linear regression. The independent variables are including culture, price and quality. Whilst, the dependent variable is consumer preferences. The results showed that the factors of culture (X1), Price (X2) and Quality of product (X3) simultaneously have a significant effect on consumer preferences toward Topo red onions.